TINJAUAN PSIKOLINGUISTIK: PERKEMBANGAN BAHASA ANAK DENGAN ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) USIA 4 TAHUN - Rahma Annisa; Widiyah; Sundawati Tisnasari (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study uses a psycholinguistic overview to investigate language development in 4 year old children with Attention Deficit Hyperactivity Disorder (ADHD). Direct interviews with interviewees were used in the qualitative research methodology of this study, and data came from interviews with biological mothers of children with ADHD. The data found from the interviews were then analysed based on psycholinguistic theory. The results of the research show that ADHD can affect the growth and development aspects of the sufferer, including the object of this research. ADHD can still be cured at the age of less than two years, by doing therapy to the doctor. ADHD children in this study experienced differences in growth and development before and after therapy. The role of parents is also important to support and support the process of growth and development of children.